2018
DOI: 10.29024/aogh.912
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mixtures of Pollutants in Mexican Children from Marginalized Urban Areas

Abstract: Background: Exposure to contaminant mixtures in developing countries is an important public health issue. Children are identified as the most susceptible group to adverse health effects due to the exposure. Objective: The aim of this study was to conduct a screening for mixture pollutants in Mexican children in urban marginalized communities. Methods: We analyzed children (aged 6-12 years old) who resided in four urban marginalized communities in San Luis Potosi, Mexico: i) Bellas Lomas (BEL), a site with vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…On the other hand, it has been reported that 70–80% of a child population living in a petrochemical area of the state of Veracruz, Mexico, has lower levels of tt-MA (0.36–0.38 mg/g Creatinine) than the levels found in this study [36]. Other studies of children from marginalized urban areas also showed lower median values of tt-MA (0.220–0.429 mg/g Creatinine [37]. Clearly, these differences are mainly due to the exposure scenario.…”
Section: Discussioncontrasting
confidence: 38%
“…On the other hand, it has been reported that 70–80% of a child population living in a petrochemical area of the state of Veracruz, Mexico, has lower levels of tt-MA (0.36–0.38 mg/g Creatinine) than the levels found in this study [36]. Other studies of children from marginalized urban areas also showed lower median values of tt-MA (0.220–0.429 mg/g Creatinine [37]. Clearly, these differences are mainly due to the exposure scenario.…”
Section: Discussioncontrasting
confidence: 38%
“…(iii) Brickmakers (TER) are located in the brick zone “Las terceras” in San Luis Potosi, Mexico (22° 12′ 04″ N, 100° 51′ 26″ W); the municipality has a population of 824,229 inhabitants; in this scenario, there are more than 120 brick kilns, which use wood tires, waste, used oil, and plastics as fuel. (Flores-Ramirez et al 2018 ) (Fig. 1c ).…”
Section: Methodsmentioning
confidence: 86%
“…It is evident that workers are a vulnerable group, requiring special attention to mitigation measurements; however, some groups of workers are especially vulnerable; those so-called precarious works, characterized by abuse of their labor rights (low salaries, without access to social security, health services, lack of training, null protection, among many other factors) (Julià et al 2017 , Kachi et al 2014 , Medina-Gómez and López-Arellano 2019 ) and which also present health risks due to high exposure to pollutants. The above, in scenarios with high degrees of marginalization, where they generally perform their work activities within the household, exposing the worker and in consequence their families (Flores-Ramirez et al 2018 , Pérez-Herrera et al 2019 ). Therefore, the objective of this research was to evaluate the mixtures of hydroxylated PAHs in precarious workers of four activities with high toxicity in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…In Mérida and Ensenada the color of urban dust has proved to be an indicator of heavy metal pollution, dark colors are more polluted than light ones (Cortés et al, 2015;Aguilar et al, 2021). In San Luis Potosí, the highest concentrations of heavy metals in urban dust have been related to the metallurgical complex and the industrial park (Aguilera et al, 2019); and heavy metals in soils could also be an important pathway of exposure (Perez-Vazquez et al, 2015;Pérez-Vázquez et al, 2015), indeed metal concentrations have been identified in children (Flores-Ramírez et al, 2018). Mexico City has been identified as polluted by heavy metals in urban dust (Delgado et al, 2019), and heavy metal concentrations have been measured in mothers and children (Lewis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%